Ejercicio terapéutico en pacientes con lesiones del manguito rotador. - Garcés Lucero, María Nayeli (2025)
Therapeutic exercise is key in the rehabilitation of rotator cuff injuries, as it improves functionality, reduces pain, and prevents relapses. Programs include joint mobility exercises, progressive strengthening, and proprioceptive training, adjusted according to the recovery phase. It has been proven that combining isotonic, isometric, and elastic resistance exercises promotes functional recovery. To support this claim, an exhaustive search was conducted in scientific databases such as Scopus, PubMed, and PEDro. Out of approximately 80 randomized clinical trials, 23 were selected based on inclusion criteria, such as being published within the last 15 years and achieving a minimum score of 6 on the PEDro scale. The reviewed studies show that therapeutic exercise is particularly effective in cases of partial or degenerative injuries when started early and tailored to the patient's needs. Additionally, its implementation in the postoperative period is essential to enhance surgical outcomes and prevent complications. Most of the analyzed clinical trials demonstrated that this intervention significantly improves shoulder pain, disability, and functionality, having a positive impact on range of motion (ROM), quality of life, and the patient’s participation in daily activities.